Research Note—Engaged Scholarship: A Signature Research Methodology for Social Work. (3rd July 2017) - Delavega, Elena; Lennon-Dearing, Robin; Neely-Barnes, Susan; Soifer, Steve; Crawford, Cicely
ABSTRACT: Social work has a rich tradition of engagement. Throughout its history, social work scholars have taken up questions that link knowledge production to its application in practice. Recently, other higher education fields have expressed interest in engagement. Yet, social work scholars have remained relatively silent about what they have to offer this new movement. This research note examines the parallels between the development of social work and the development of higher education, the ways social work is an engaged discipline, how engaged scholarship relates to translational research and evidence-based practice, and the implications of engaged scholarship for tenure and promotion. We argue that engaged scholarship should be considered the signature research methodology of social work.